Masinag concentrate convenience center and transit exchange - Navarro, Justin Benedict G.
As the world transitions to the 21st century, the way architecture is perceived and built evolves as well. Bernard Tschumi, proposed to re-evaluate the definition of programming in architecture, to consider the emergent cencepts of what he referred to as "cross-programming" and "dis-programming". The theme of UP College of Architecture undergraduate thesis celebrates this movement, by applying Tschumi's concepts in an agenda based design rather than the conventional typology based programming. This thesis study focuses on the Masinag District, in Antipolo, Rizal. Masinag district is bounded by barangays Mayamot and Mambugan, and is intersected by Marcos and Sumulong Highway. Due to its location and direct access to both Antipolo and Metro Manila, the site is known as the gateway to Antipolo. What makes this site a viable one is the fact that the new LRT-2 Masinag station would be located here. By naming the site's issues and opportunities, the 4 agendas were formulated ; connectivity, community, commerce, and sustainability. These agendas were used to form the different spaces needed by the site. Ultimately, the development was conceived to be a transit oriented development which connects the whole district together, and celebrates the image of Masinag as the Gateway to Antipolo.